Natural Resources Exploitation in Sulfate-Resisting Portland Cement Manufacturing: Towards Quality Improvement and Reduction of Environmental Impact - Labidi, Islem; Megriche, Adel (Frontiers in Chemistry, 2022)
Sulfate-resisting (SR) Portland cement is commonly used in building works to improve concrete’s durability against external sulfate attack. This attack is considered a very serious chemical aggression that causes damage and cracking of concrete structures. These special cements have a very particular mineralogical composition, C3A ≤ 3% and (2C3A + C4AF) ≤ 20%, which makes the cementitious matrix resistant to sulfate attack. This kind of product is very difficult to manufacture since low alumina (C3A) necessitates the use of a high kiln temperature in order to keep a sufficient liquid phase necessary to maintain the stability of the cement manufacturing process. In this context, this study aims to optimize SR Portland cement raw meals using natural materials collected from different regions in Tunisia, mainly ordinary limestone, siliceous limestone, black marl, grey marl, iron ore, and natural fluorapatite. The collected specimens were characterized by an X-ray fluorescence spectrometer in order to determine its elemental chemical composition. The optimization of the SR Portland cement raw meal combinations was done by means of a calculation tool based on the chemical composition of each used raw material and the variation of burning modules (LSF, SIM, and ALM). It has been found that natural fluorapatite integration (0%–15%) in raw mix preparation leads to the raw meals required for the SR Portland cement standard (C3A ≤ 3% et 2 C3A + C4AF ≤ 20%). Moreover, it was shown that the estimated SR raw meals ensure the cement manufacturing process stability (acceptable burning modules “LSF = 100; SIM = 3; ALM = 0.91 and sufficient liquid phase) and decrease the CO2 emissions in cement production.